Crime under lockdown: the impact of COVID-19 on citizen security in the city of Buenos Aires - Perez-Vincent, Santiago M. (Criminology & public policy, 2021)
This paper studies the impact of the COVID-19 pandemic and the subsequent lockdown on criminal activity in the City of Buenos Aires, Argentina. Following quarantine restrictions, we find a large, significant, robust, and immediate decline in property crime reported to official agencies, police arrests, and crime reported in victimization surveys. We observe no significant change in homicides, and a significant increase in arrests for “resistance to authorities”. The decrease in criminal activity was greater in business and transportation areas, but still large in commercial and residential areas (including informal settlements). After the sharp and immediate fall, crime recovered but, by the end of 2020, it had not reached its initial levels. The arrest data additionally shows a reduction in the distance from the detainee's address to the crime location, and a fall in the number of detainees from outside the City of Buenos Aires. Crime became more local as mobility was restricted.